The Analysis of Equivalence of Song Lyrics from English to Indonesian Song By Maher Zain - Yana Sofianti; Baharudin Baharudin; Lalu Jaswadi Putera (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study aims to examine and analyses the equivalence of meaning between English and Indonesian lyrics of three Maher Zain songs: